Characterization of a novel thermostable alkaline lipase derived from a compost metagenomic library and its potential application in the detergent industry - Li, Qing-Qing; Zhu, Zi-Ran; Liu, Qing-Gang; An, Yu-Ting; Wang, Yi-Xiang; Zhang, Shu-Bin; Li, Gang (Frontiers in Microbiology, 2022)
A novel lipase, Lip54q, which belongs to the VIII family of lipolytic enzymes, was identified by functional screening using a metagenomic library of compost soil samples. To explore the enzymatic properties of Lip54q, the enzyme was heterogeneously expressed in Escherichia coli with a high expression level of 720 mg/L. The recombinant enzyme showed the highest activity against a C10 substrate at pH 9.0 and 47 C, and was stable at temperatures ≤50 C and pH 8.0-11.0. Of particular interest, the surfactants, Tween-20, Tween-80 and Tritonx-100, exhibited strong promoting effects on Lip54q activities regardless of whether low concentrations (0.1%) or high concentrations (10%) were used. Application studies of Lip54q using six commercial detergents indicated that the enzyme had strong tolerance and immersion resistance to all six detergents. The results of oil-stain removal experiments suggested that addition of the enzyme to various commercial detergents could significantly improve the abilities of these detergents to remove oil-stains. Furthermore, the results of a molecular docking analysis of Lip54q showed that both the C10 substrate and linoleic acid molecules could form hydrogen bond interactions with the catalytic amino acids, Ser-268, Glu-168, and Asp-192, in the catalytic center of the enzyme, and the hydrogen bond distances were short, which were conducive to the formation of a stable complex between enzyme and substrate, thus increasing the activity of the enzyme to such substrates. These results 1ay a good foundation for application of this enzyme in the detergent industry in the future.